Model of School Management Based on Islamic Education - Iyus Herdiana Saputra; Tri Ermayani; Edi Sunjayanto Masykuri (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2020)
This research is revieweing the school management based on islamic education. It aims to obtain an overview of the implementation of Islamic boarding school education and a model for the development of education management at the Darul Hikmah Kutoarjo Islamic boarding school. This research problem will focus on how to plan, organize, coordinate, and control Islamic boarding schools. To answer the research problem, this type of qualitative research is used with a descriptive-analysis approach. The results of this study indicate that: a) The Darul Hikmah Islamic Boarding School Education Model is a pesantren education under the auspices of the Darul Hikmah Kutoarjo Foundation. The education pattern of Darul Hikmah Islamic boarding school isa boarding-based modern Islamic boarding school education pattern. In developing the management of the Darul Hikmah Islamic Boarding School, it uses the Target Based Management (MBS) or Management by Objective (MBO) model. The target to be achieved is to focus on education; c) To achieve this education, the management steps taken are: a) Planning. The planning model developed by the Darul Hikmah IslamicBoarding School is a strategic planning model consisting of planning, programming, and budgeting systems; b) Organizing. Organizing is carried out under a decentralized system in the division of powers and tasks and their development; 3) Coordination. Coordination is carried out in an effort to unify a series of activities in the organization of pesantren in order to increase cooperation and togetherness among organizational officials as much as possible; 4) Supervision. Supervision includes monitoring, supervision, evaluation, reporting, and follow-up of assessment results.